The biogeographical kingdoms and regions of the world - Loidi, Javier; Vynokurov, Denys (Mediterranean Botany, 2024)
This paper presents an updated overview of the world’s biogeographical realms and regions in the terrestrial domain. It incorporates new data on floristic and vegetation aspects, along with recent regional information, which has emerged in the decades following the influential maps created by A. Takhtajan and R. Good. We elucidate the various biogeographic scales, ranging from kingdoms to districts, and outline the specific criteria that define them. We delve into the criteria used for characterizing the kingdoms and regions, with a particular focus on their floristic content, evolutionary background, and vegetation patterns, expressed through biomes and subbiomes. Additionally, we discuss the climatic conditions and their variability within and between these units. Our study identifies six kingdoms and 42 regions that are recognized for the entire planet and provides a concise summary for each of them.